An approach to building MSMEs in Plosowahyu Village involves socializing social media management - Nur Ilmayasinta; Dimas Tata Muktia; Eka Putri Damaiati (Unika Santu Paulus Ruteng, 2022)
In the era of the fourth industrial revolution, technology is crucial. The use of technology can benefit businesses, particularly Micro, Small, and Medium Enterprises (MSME) by making it simpler for them to promote their goods and provide information about them. Unfortunately, there are still a lot of residents of Plosowahyu Village who are unable to effectively use technology. As a result, the author feels compelled to perform community service in order to help the residents of Plosowahyu Village understand the value of technology, and improve their ability to manage social media as a tool for promoting Micro, Small, and Medium Enterprises (MSME) and create graphic designs as a useful means of information sharing between hamlets and villages. The target of this socialization includes Micro, Small, and Medium Enterprises (MSME) activists in Plosowahyu Village and youth-focused social organizations. The process of implementation entails socialization, education, and help with creating tasks and programs. Based on the results of the tasks, all participants are capable of independently producing graphic designs and comprehending the significance of technology throughout the industrial revolution. 4.0.